Respuesta :

DeanR

[tex]4x^2-5=3x+4 [/tex]

[tex]4x^2 - 3x - 5 - 4 = 0[/tex]

[tex]4x^2 - 3x -9 = 0[/tex]

[tex] x= \dfrac{3 \pm \sqrt{3^2 - 4(4)(-9)}}{2(4)} [/tex]

[tex]x = \frac 1 8 (3 \pm \sqrt{9(1 + 16)})[/tex]

[tex]x = \frac 1 8 (3 \pm 3\sqrt{17})[/tex]


Answer:

Solutions are 1.92 and -1.17

Step-by-step explanation:

The general solutions of quadratic equation of the form ax²+bx+c = 0 is given by [tex]\frac{-b+\sqrt{b^2-4ac} }{2a}[/tex] and [tex]\frac{-b-\sqrt{b^2-4ac} }{2a}[/tex]

Here the the equation is 4x²-5 = 3x + 4

On rearranging

             4x²-3x-5-4 = 0

             4x²-3x-9 = 0

Comparing with ax²+bx+c = 0, we will get a = 4, b = -3 and c = -9

The solutions are given by

     [tex]\frac{-(-3)+\sqrt{(-3)^2-4*4*(-9)} }{2*4}[/tex] and  [tex]\frac{-(-3)-\sqrt{(-3)^2-4*4*(-9)} }{2*4}[/tex]

     [tex]\frac{3+\sqrt{153} }{8}[/tex] and  [tex]\frac{3-\sqrt{153} }{8}[/tex]

     1.92 and -1.17

ACCESS MORE